Concepts in financial management, banking & finance - Nwanna, Ifeanyi O. (Lagos, Nigeria : Goldtrust Ventures Ltd., 1999)
The book presents a systematic account of some principles and concepts involved in modern studies of Business Management, Finance, Banking and Investments.
Includes bibliographical references.
rua 25/02/15
Loans
Keywords: Corporations - finance; Financial management; Banks & banking; Finance